The relationship between mitochondrial DNA haplotype and its copy number on body weight and morphological traits of Wuliangshan black-bone chickens - Wenpeng Li; Zhen Yang; Chao Yan; Siyu Chen; Xingbo Zhao (PeerJ)
Mitochondria play a pivotal role as carriers of genetic information through their circular DNA molecules. The rapid evolution of the D-loop region in mitochondria makes it an ideal molecular marker for exploring genetic differentiation among individuals within species and populations with close kinship. However, the influence of mtDNA D-loop region haplotypes and mtDNA copy numbers on phenotypic traits, particularly production traits in chickens, remains poorly understood. In this comprehensive study, we conducted D-loop region amplification and sequencing in the blood mitochondria of 232 female Wuliangshan black-bone chickens. Our investigation identified a total of 38 haplotypes, with a focus on 10 haplotypes that included more than five individuals. We meticulously analyzed the correlations between these haplotypes and a range of traits, encompassing body weight, tibial length, tibial circumference, body oblique length, chest width, and chest depth. The results unveiled significant disparities in specific tested traits across different haplotypes, indicating a tangible association between mtDNA haplotypes and traits in chickens. These findings underscore the potential impact of mitochondrial DNA variations on energy metabolism, ultimately leading to divergent chicken phenotypes. Furthermore, our examination revealed positive correlations between mtDNA copy numbers and tested traits for select haplotypes, while other haplotypes exhibited non-uniform relationships between traits and mtDNA copy numbers. In addition, phylogenetic analysis disclosed the involvement of two subspecies of red jungle chicken in the origin of Wuliangshan black-bone chickens. Consequently, our research contributes novel insights into mitochondrial genomic selection, augments comprehension of the roles played by haplotypes and mtDNA copy numbers in chicken population genetics and phylogenetic analysis, and furnishes fundamental data crucial for the preservation and provenance determination of black-bone chickens.